Alpha-amylase as the culprit in an occupational mealworm allergy case - Ganseman, Eva; Ieven, Toon; Frans, Glynis; Coorevits, Lieve; Pörtner, Noëmie; Martens, Erik; Bullens, Dominique MA; Schrijvers, Rik; Breynaert, Christine; Proost, Paul (Frontiers in Allergy, 2022)
Background Occupational allergy has been described in employees working in contact with mealworms in pet stores, live fish bait or infested stored grains and recently, in mealworm farming for animal feed and human consumption. Mealworm allergens linked to occupational allergy are troponin C, cockroach-like allergen, tropomyosin, arginine kinase, early-staged encapsulation inducing- and larval cuticle proteins. Objective We report a case of occupational mealworm allergy and studied the culprit component. Methods Diagnosis was done by skin prick, specific IgE, basophil activation and lung function testing. Allergen purification was performed by anion-exchange chromatography and immunoblotting with patient IgE. Allergens were identified by in-gel trypsin digest and tandem mass spectrometry. Allergenicity and specificity further confirmed by IgE inhibition and passive basophil activation experiments. Results We describe a new case of occupational mealworm allergy in a laboratory worker, with sensitization to different developmental stages and derivates of the mealworm. In basophil activation tests, the majority of patient's basophils (69%–91%) degranulated upon stimulation with the lowest concentration of mealworm extracts (0.16 µg/ml). Despite strong sensitization to mites, the patient did not show cross-reactivity to other insects. We were able to identify alpha-amylase as the main allergen and through inhibition experiments, we demonstrated that low amounts (0.1 µg/ml) of this allergen could strongly inhibit mealworm specific IgE by 79.1%. Moreover, passive BAT experiments demonstrated the IgE-alpha-amylase interaction to be functional, inducing up to 25.5% degranulation in healthy donor basophils. Conclusion Alpha-amylase can be identified as the responsible allergen in this specific case of occupational mealworm allergy.